Peningkatan Kemampuan Bahasa Anak Usia 5-6 Tahun melalui Kegiatan Market Day di KB Karya Akbar Mandiri - Yusmaniar, Yusmaniar; Rahayu, Swandra; Rizka, Nelti (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to improve the language and communication skills of children aged 5-6 years through the implementation of Market Day activities. This research is Classroom Action Research (CAR) conducted in two cycles. The subjects were 15 children at KB Karya Akbar Mandiri, Indragiri Hilir. Data were collected through participatory observation and documentation, then analyzed using descriptive quantitative methods. The findings showed a significant increase in language proficiency in each cycle. In the pre-cycle stage, the majority of children (12 children) were still in the Starting to Develop (MB) category. After the intervention in Cycle I, the achievement percentage increased to 60.8%. The peak improvement occurred in Cycle II, reaching 84.9%, with 11 children achieving the Developed Very Well (BSB) category. Market Day activities are proven effective in stimulating children's interactive communication skills through contextual buying and selling interactions.